2023
DOI: 10.3390/nu15051179
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Calprotectin Elevations Associated with Food Intolerance/Malabsorption Are Significantly Reduced with Targeted Diets

Abstract: Inflammatory bowel disease (IBD) involves two clinically defined entities, namely Crohn’s disease and ulcerative colitis. Fecal calprotectin (FCAL) is used as a marker to distinguish between organic IBD and functional bowel disease in disorders of the irritable bowel syndrome (IBS) spectrum. Food components may affect digestion and cause functional abdominal disorders of the IBS spectrum. In this retrospective study, we report on FCAL testing to search for IBD in 228 patients with disorders of the IBS spectrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…It is common in inflammatory bowel disease (IBD) and in RA research to use commercially available kits to assess zonulin, a marker of intestinal permeability, or calprotectin, a marker of intestinal inflammation, in blood or stool [ 8 , 23 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. However, there are insufficient data regarding which (fecal or serum) may be the more valuable diagnostic and prognostic biomarker for RA.…”
Section: Discussionmentioning
confidence: 99%
“…It is common in inflammatory bowel disease (IBD) and in RA research to use commercially available kits to assess zonulin, a marker of intestinal permeability, or calprotectin, a marker of intestinal inflammation, in blood or stool [ 8 , 23 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. However, there are insufficient data regarding which (fecal or serum) may be the more valuable diagnostic and prognostic biomarker for RA.…”
Section: Discussionmentioning
confidence: 99%
“…12 As antihypertensive drugs are used to treat high blood pressure, they inevitably have adverse effects, such as sprue-like enteropathy when taking IRB and OLM. [13][14][15] Moreover, consumers who are already taking antihypertensive medications can be accidently overdosed with drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Gaining a deeper understanding of the impact of food intolerances on patients with IBD is crucially important. Recent research has shown that levels of fecal calprotectin, a widely used marker for distinguishing between functional and organic bowel disorders, as well as assessing the severity of IBD, may be elevated in patients with lactose intolerance, fructose malabsorption, or histamine intolerance [5].…”
Section: Introductionmentioning
confidence: 99%